2007
DOI: 10.1186/1472-6874-7-15
|View full text |Cite
|
Sign up to set email alerts
|

Associations of depression and depressive symptoms with preeclampsia: results from a Peruvian case-control study

Abstract: Background: Preeclampsia involves endothelial dysfunction, platelet dysfunction/activation and sympathetic over-activity similar to cardiovascular disorders (CVD). Depression, an independent risk factor for progression of CVD, was found to be associated with an increased risk of preeclampsia among Finnish women. We examined the relation between depression/depressive symptoms and preeclampsia risk among Peruvian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 21 publications
(27 reference statements)
9
67
0
6
Order By: Relevance
“…Kurki et al [8] observed that depression and anxiety or both were associated with an increased risk of preeclampsia. Qiu et al illustrated that depression and depressive symptoms were related to an increased risk of preeclampsia [9].…”
Section: Discussionmentioning
confidence: 99%
“…Kurki et al [8] observed that depression and anxiety or both were associated with an increased risk of preeclampsia. Qiu et al illustrated that depression and depressive symptoms were related to an increased risk of preeclampsia [9].…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio realizado en Perú en 2004 se encontró una prevalencia de depresión mayor de 13,5% en mujeres con 32 semanas de gestación que vivían en la comunidad (15), mientras en otro realizado en una sala de maternidad de Perú, esta proporción fue de 17,0% (16). Estos porcentajes son mayores que los informados para la depresión postparto, que van de 8,1% a 9,1% (17)(18)(19)(20)(21).…”
Section: Discussionunclassified
“…A esto puede contribuir que con frecuencia no se documentan adecuadamente los episodios depresivos y su intensidad. Esta situación tiene un impacto negativo sobre la salud de la madre y el hijo, provoca una mayor carga social, clínica y económica, e impide diseñar e implementar intervenciones adecuadas para la prevención y el tratamiento oportunos de las complicaciones asociadas (15). El estudio de la depresión mayor durante el embarazo debe aportar datos útiles que permitan poner en práctica programas eficaces de prevención y tratamiento temprano que contribuyan a mejorar la calidad de la vida de las embarazadas.…”
Section: Introductionunclassified
“…Egy 623 primipara bevonásával készült kutatás eredményei szerint a várandósság alatti depresszió 2,5-szeres, a szorongás 3,2-szeres kockázatot jelent a praeeclampsia kialakulására nézve [28]. Qiu és mtsai vizsgálati eredményei szerint a terhességük alatt mérsékelt depressziós tüneteket mutató nőknek 2,3-szer, a súlyo-sabb tüneteket mutatóknak 3,2-szer nagyobb kockáza-tuk volt a praeeclampsia kialakulására [29]. Kharaghani és mtsai kutatásában a középsúlyos, illetve súlyos depresszióval diagnosztizált nők 2,5-szer nagyobb valószí-nűséggel lettek praeeclampsiásak várandósságuk során [30].…”
Section: A Pszichés Faktorok Vizsgálata Praeeclampsiábanunclassified
“…Emellett a betegség kialakulása közvetlenül összefügg olyan egyes, pszichés zavarokra jellemző egészségkárosí-tó magatartásokkal, mint a terhesség előtti és alatti dohányzás, a nem megfelelő táplálkozás és vitaminbevitel, valamint a fi zikai inaktivitás [29]. Haelterman és mtsai vizsgálatában azoknál a nőknél, akik fokozottabb fi zikai vagy pszichés munkahelyi stressznek voltak kitéve, nagyobb eséllyel alakult ki praeeclampsia [32].…”
Section: A Pszichés Faktorok Vizsgálata Praeeclampsiábanunclassified